KERAGAAN PEMIJAHAN ANTAR TIGA STOK UDANG HUNA MERAH (Cherax quadricarinatus von Martens) - Otong Zenal Arifin; Titin Kurniasih (BERITA BIOLOGI, 2013)
This research aimed to obtain information on the variability of crossbred resulted from three stocks of red claw (Cherax quadricarinatus von Martens). This research was performed at Research and Develepment Institute for Freshwater Aquaculture.Nine population consists of tree true breed and six reciprocal breed were resulted from the crossbreeding between the three stocks from Jakarta, Bali and Sukabumi.Results showed that the crossbred between Bali female parent and Jakarta male parent had the highest number of larvae / kg weight of female parent compared to the other crossbred. Between the female parent category, the Bali female parent showed the highest number of the larvae yielded, and between the male parent category, the Sukabumi male parent did. There was no significant different between the crossbred on the respon of growth performance. The highest heterosis on the number of larvae was achieved by the crossbred between Bali and Jakarta (25.8%) while the crossbred between Bali and Sukabumi performed the negative heterosis (-17.6%).Based on the calculation of the number larvae per kilogram weight of the parent, the highest heterosis was achieved by the crossbred Bali-Sukabumi (98.4%).The heterosis on the final weight and length showed the poor result, while on the respon of the specific growth rate showed negative result.It can be concluded that this undertaken hybridization did not provided the significant positive heterosis effect except for the number of larva per unit weight of parent.